Ultrasound flow phantom for transcranial Doppler: An assessment of angular mismatch effect on blood velocity measurement in comparison to optical particle image velocimetry - Hashuro, Muhammad Shiddiq Sayyid; Daibo, Kotaro; Ishii, Takuro; Saijo, Yoshifumi; Ohta, Makoto (Frontiers in Physics, 2023)
Detecting abnormal blood flow is possible through transcranial Doppler (TCD) ultrasound by measuring blood velocity in cerebral arteries. Velocity measurements are at the highest precision when the direction of blood flow coincides with the ultrasound beam. However, because TCD is typically performed blindly (i.e., without a B-mode), a 0° interrogation angle is usually assumed. This leads to a common issue of angular mismatch.This study quantitatively shows the angular mismatch effects on the measured velocities using a TCD ultrasound flow phantom compared with the velocities measured by optical particle image velocimetry (PIV) as control. Resulting errors with and without ultrasound machine angular correction were also considered. An ultrasound phantom developed by combining polyvinyl alcohol hydrogel (PVA-H), quartz glass as a scatterer, and a gypsum plate as a skull bone was utilized to approximate the middle cerebral artery TCD measurement from the temporal window. The PVA-H and quartz glass compositions were controlled to achieve transparency and enable PIV velocity measurement. Then, TCD velocity measurement was conducted on several interrogation and mismatch angles. Comparison results revealed that without an ultrasound machine angle correction, all measurements yielded underestimation with 73.9% at the highest in the 80° interrogation window at the 130 mL/min flow. On the other hand, with the correction, the errors in almost all angles were comparatively lower; however, at 80° at the 124 mL/min flow, a maximum overestimation rate of 113.7% was found, showing a larger error magnitude. Therefore, we find that angular mismatch, especially in larger angles, leads to inaccurate velocity measurements in TCD. Our results suggest that despite angle correction, velocity errors may still occur when the interrogation angle changes.